Management of Solid Home Waste in Rural Environment - Aguilar-Botia, Karent-Dayana; Hernández-Botia, Faber-Andrés; González-Santos, Wilson (Universidad Pedagógica y Tecnológica de Colombia, 2023)
It is estimated that global solid waste management is still insufficient due to factors such as: the increase in generation, consumption habits, production systems and the lack of alternatives for its use and/or treatment. Throughout this time, strategies have been designed and implemented that seek to mitigate this problem, but these are mostly implemented in urban areas, although rural areas are no stranger to this reality. Therefore, a case study of the current management given to solid waste in three villages of the municipality of Mongua, corresponding to Centro, Duce and Monguí, was carried out. The information was collected through surveys, semi-structured interviews and participatory workshops, with the participation of the members of the Huerto Alto Andino Farmer Association. At the end of the exercise, it was determined that the burning of solid waste in charcoal stoves or in bonfires is the most common practice in homes, as well as the use of organic waste to produce organic fertilizer and use it in their orchards and crops, insofar as to recyclable waste, it is evident that they are sold or some are buried, a practice that affects health, the environment and the economy of the territory. In this sense, collective environmental sensitivity commitments were made and, as a message to the municipal authorities, the call is made to contribute to adequate and comprehensive management processes of solid waste in rural areas that promote their sustainable development